2013
DOI: 10.1111/all.12110
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genetic and metabolite profiling analysis suggests altered phosphatidylcholine metabolism in asthma

Abstract: Our study demonstrated the potential of metabolomics to infer asthma-related biomarkers by the identification of potentially deregulated phospholipids that associate with asthma and asthma risk alleles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 31 publications
8
56
0
Order By: Relevance
“…Previous metabolomics studies revealed metabolic alteration in the asthma exacerbated condition [32,[34][35][36]. Histidine, trimethylamine N-oxide, phenylacetylglycine, threonine, 4-aminohippurate and methylamine were decreased, whereas creatine, glucose, hippurate, alanine, glycolate, succinate, myo-inositol, dimethylamine, formate, homovanillate, acetylcarnitine, taurine, lactate, oxaloacetate, cis-aconitate, 2-methylglutarate, tyrosine, 1-methylhistamine, 2-hydroxyisobutyrate, acetone, carnitine, 3-methyladipate and 2-oxoglutarate were increased in asthmatic children during acute exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous metabolomics studies revealed metabolic alteration in the asthma exacerbated condition [32,[34][35][36]. Histidine, trimethylamine N-oxide, phenylacetylglycine, threonine, 4-aminohippurate and methylamine were decreased, whereas creatine, glucose, hippurate, alanine, glycolate, succinate, myo-inositol, dimethylamine, formate, homovanillate, acetylcarnitine, taurine, lactate, oxaloacetate, cis-aconitate, 2-methylglutarate, tyrosine, 1-methylhistamine, 2-hydroxyisobutyrate, acetone, carnitine, 3-methyladipate and 2-oxoglutarate were increased in asthmatic children during acute exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a causal link between PC and lung surfactants levels, where reduction in PC level can lead to worsening in lung functions in asthma (Wright et al 2000;Ried et al 2013). BALF level of PC dipped, but its downstream metabolite choline level elevated in experimental asthma .…”
Section: Discussionmentioning
confidence: 99%
“…From our study we can clearly see a trend of suppression of anti-inflammatory pathways by prednisone treatment and an increase in membrane phospholipid synthesis (Figure 5). Altered PC metabolism has been suggested in asthma with increase in level of PC and decrease in level of lyso-PC [39] and Crohn’s disease where phospholipids were increased [40]. Differences in free choline and PC level in serum have been associated with early markers of risk of having cardiovascular disease (CVD) [41].…”
Section: Discussionmentioning
confidence: 99%